Integrated profiling methods for identifying the targets of bioactive compounds: MorphoBase and ChemProteoBase. Issue 5 (21st March 2016) - Muroi, Makoto; Futamura, Yushi; Osada, Hiroyuki
Abstract : Target identification of new bioactive compounds has been achieved by both our direct and indirect approaches. Here, we highlight the utility of the latter approaches, MorphoBase and ChemProteoBase. Abstract : Covering: up to the end of 2015. Many useful compounds from natural products have been discovered through phenotype-based screening. However, the target identification process for compounds is laborious and time-consuming. With the development of new equipment and methodologies for biological analyses, a variety of profiling methods that utilize large sets of experimental data have been established. Here, we highlight the utility of our identification approaches, MorphoBase and ChemProteoBase.